Projected water demand by 2050 in South Gobi region of Mongolia - Badarch, Ayurzana; Ariya, Elbegjargal; Dashjamts, Ariun-Erdene; Gansukh, Batzorig (Proceedings of the Mongolian Academy of Sciences, 2021)
The South Gobi region (including Umnugovi, Dundgovi and Dornogovi aimags - provinces) of Mongolia is becoming a leading region of the nation’s economic and social development. Water resources play an important role in ensuring sustainable economic development of the South Gobi region. In the South Gobi region, lack of proven groundwater resources, data on water extraction and consumption makes it difficult to accurately identify risks and to manage limited resources for sustainable development. Based on the available historical data between 2015 and 2019 on water resources and water use, the water demand in this region has been projected up to the year 2050 on the basis of dynamic modelling of water management, including major stakeholders, country’s sustainable economic development vision up to the year 2050, and the impact of climate change. The model predicts continued increasing demand for mining, agricultural, industrial and social services and rural water demands, while gradual decline for the livestock water demand was projected after the gradual increase in the first half of the period. Basing on the system dynamic modelling of water management, it can be said that the groundwater resources of the South Gobi region may not be able to meet the above needs after 2037. Economically feasible measures and managements to prevent the risk of water scarcity before water shortage happens are proposed based on the results of the model.